Chronic hexavalent chromium exposure induces oxidative stress-mediated molecular cascades in Thymallus grubii gills: evidence from integrated transcriptomics and metabolomics - Shang, Xinchi; Che, Xinghua; Ma, Kai; Ma, Bo; Sun, Huizhi; Wu, Wenhua; He, Hailong; Xing, Meiqi; Xu, Wei; Zhang, Yongquan (Frontiers in Immunology, 2025)
IntroductionCr(VI) is a heavy metal contaminant, can diffuse to ecosystems and harm aquatic animals. Gills, as a vital organ in direct contact with the aquatic environment, have become a key target tissue for assessing the toxicological effects of heavy metal pollution of water bodies due to their sensitivity to heavy metal exposure. However, 3the effects of Cr(VI) on the gill tissues in fish have been less studied. In this study, we revealed the multiple effects of chromium toxicity by assessing the oxidative damage, transcriptomic and metabolomic changes of Cr(VI) on gill tissues of Thymallus grubii.MethodsA total of 270 fishes were stratified into three experimental groups: control group, low-concentration exposure group (0.2 mg/L), and high-concentration exposure group (1 mg/L). In this study, we revealed the multiple effects of chromium toxicity by assessing the oxidative damage, transcriptomic and metabolomic changes of Cr(VI) on gill tissues of Thymallus grubii.ResultsCr(VI) stress can lead to gill damage with significant reduction in gill filament thickness, significant thinning of gill lamellae, and congestion of epithelial blood vessels. Cr(VI) stress significant increases in H2O2 and MDA levels and significant decreases in antioxidant enzyme activity levels (SOD, GSH-Px, and T-AOC) and energy metabolism-related ATPase activity levels (Na+K+-ATPase, Ca2+-ATPase, and Mg2+-ATPase). Cr(VI) stress induced disturbances in gill arachidonic acid metabolism leading to the release of pro-inflammatory metabolites (e.g., thromboxane A2 and prostaglandin J2) accompanied by the accumulation of oxidised glutathione. However, the synthesis of metabolites with anti-inflammatory/antioxidant functions (e.g. GABA, quinidine and l-artitic acid) was reduced. Transcriptomics and metabolomic coanalyses revealed that Cr(VI) induced PPAR-γ inactivation to deregulate COX-2, which disrupted arachidonic acid metabolic pathways, leading to oxidative stress, apoptosis, and release of inflammatory factors. Disorders of arachidonic acid metabolism led to the release of proinflammatory metabolites (such as thromboxane A2 and prostaglandin J2), and decreased levels of reduced glutathione.DiscussionThe effects of Cr(VI) exposure on gill gene expression and metabolism were analysed using RT-PCR, transcriptomic, and metabolomic approaches. In summary, we better understand the toxic effects of Cr(VI) on gill tissues of aquatic animals. Targeted activation of PPAR-γ and supplementation with anti-inflammatory metabolites such as GABA, quinidine and l- artitic acid may be potential intervention strategies to reverse Cr(VI) toxicity.